TISSUE EXPRESSION OF INTERLEUKIN-17 SIGNIFICANTLY AND INDEPENDENTLY AFFECTS PRURITUS IN PSORIATIC PATIENTS: A CLINICOPATHOLOGICAL CORRELATION - HUSSEIN ROSHDY, OSSAMA; ABDEL-BARY, AHMED; EL-ACHY, SAMAR NABIL; WAHAB IBRAHIM, ASMAA ABDEL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This study aimed at the evaluation of pruritus and its intensity and aggravating factors in psoriatic patients with the assessment of its relation to interleukin-17 (IL-17) expression in psoriatic lesions. Methods: The study included 50 patients with psoriasis vulgaris. A questionnaire was used for the evaluation of pruritus and its effect on the quality of life. Severity of pruritus was assessed by the visual analog scale (VAS) while clinical severity of psoriasis was assessed using psoriasis area severity index (PASI) score. Tissue immunohistochemical expression of IL-17 was assessed in psoriatic lesions and in 20 normal skin biopsies included as control. Results: Pruritus was encountered in 92% of psoriatic patients studied, 45.5% of them considered emotional stress as the main pruritus aggravating factor. Pruritus had influenced the daily activity and sleep in 91.3% of the studied patients. Mean VAS in studied cases was 5.70 ± 2.76. VAS grades were significantly associated with PASI scores and IL-17 tissue expression on univariate analysis. On multilogistic regression analysis, both IL-17 and PASI scores emerged as independent influencers of pruritus. Conclusion: Pruritus is a common symptom that affects the quality of life in psoriatic patients. IL-17 is an independent aggravating factor of pruritus in those patients. To the best of our knowledge, this is the first study evaluating the tissue expression of IL-17 in relation to pruritus. Pruritus treatment should be one of our goals while managing the psoriatic patients and anti-IL-17 may play a pivotal role in this field.